The Quality of Work Life and the Relationship Motivation for Achievement of Faculty Members Hail University in the Kingdom of Saudi Arabia - Alosaimi, Jaza Obeid; Alaghdaf, Ayesha Alnemah (Journal of Educational and Psychological Sciences, 2023)
The study aimed to find out The Quality of Work Life and the relationship Motivation for Achievement of Faculty Members Hail University. To achieve the objectives of the study, the researchers used the scale of quality of work life by (Hamadnh, 2019) which consisted of (27) items, divided into Five dimensions: (leadership style, stability and job security, career promotion, the balance between university work and social life, professional development) and scale motivation for achievement by: (Bouaziz, 2015), The sample consisted of faculty members Hail university. The data were analyzed through the means and standard deviations, T-test value, ANOVA and correlation coefficients. Results there are statistically significant differences in terms of the quality of professional life, attributed to the sex variable in favor of the females. however, there are no differences in the quality of professional life based on academic rank. Also, there are no statistically significant differences in the motive for achievement for faculty members at Hail University based on sex and academic rank variables. showed a statistically significant correlation between the quality of professional life and the motive for achievement for faculty members at Hail University, The study recommended a set of recommendations, the most prominent of which is the necessity of providing leadership style in universities by granting powers compatible with the capabilities and circumstances of faculty members to facilitate work with outstanding performance.
Keywords: quality; work life; motivation; achievement